2008
DOI: 10.1177/095632020801900301
|View full text |Cite
|
Sign up to set email alerts
|

Bevirimat: A Novel Maturation Inhibitor for the Treatment of HIV-1 Infection

Abstract: Existing antiretroviral treatments for HIV type-1 (HIV-1) disease are limited by problems of resistance and drug-drug interactions. Bevirimat is a novel HIV-1 maturation inhibitor with a mechanism of action that is distinct from other antiretroviral agents. Specific inhibition of the final rate-limiting step in Gag processing by bevirimat prevents release of mature capsid protein from its precursor (CA-SP1), resulting in the production of immature, non-infectious virus particles. Bevirimat inhibits replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 31 publications
0
66
0
Order By: Relevance
“…BVM targets the HIV-1 Gag CA-SP1 boundary region by blocking viral protease cleavage of SP1 from the CA-SP1 precursor and inhibiting release of the mature CA protein, which is the final step required for virion maturation. Despite the novel mechanism of action and initial progress made in small-scale clinical trials (11)(12)(13)17), further development of BVM has encountered unexpected challenges in the clinical setting, because patients whose viruses contain genetic polymorphisms in the Gag SP1 (positions 6 to 8) protein do not respond well to BVM treatment (3,10,14,16). These three residues (glutamine-valine-threonine [QVT]) are referred to as the SP1 polymorphism motif.…”
Section: -O-(3ј3ј-dimethylsuccinyl) Betulinic Acid (Dsb) Also Knowmentioning
confidence: 99%
“…BVM targets the HIV-1 Gag CA-SP1 boundary region by blocking viral protease cleavage of SP1 from the CA-SP1 precursor and inhibiting release of the mature CA protein, which is the final step required for virion maturation. Despite the novel mechanism of action and initial progress made in small-scale clinical trials (11)(12)(13)17), further development of BVM has encountered unexpected challenges in the clinical setting, because patients whose viruses contain genetic polymorphisms in the Gag SP1 (positions 6 to 8) protein do not respond well to BVM treatment (3,10,14,16). These three residues (glutamine-valine-threonine [QVT]) are referred to as the SP1 polymorphism motif.…”
Section: -O-(3ј3ј-dimethylsuccinyl) Betulinic Acid (Dsb) Also Knowmentioning
confidence: 99%
“…Distinct morphological intermediates have not been detected for wild-type (wt) HIV-1, indicating that maturation is a rapid process. The function of individual cleavage sites has therefore been mainly investigated by introducing mutations that block processing at specific sites or by using the drug bevirimat (31), which selectively inhibits processing between CA and SP1. These studies showed that cleavage sites separating MA and CA, CA and SP1, and SP1 and NC are all essential for viral infectivity (1,24,39,48).…”
mentioning
confidence: 99%
“…For example, in the case of bevirimat, a well-studied HIV-1 maturation inhibitor that blocks the cleavage between CA and p2, even a partial blockage at this cleavage site can elicit a significant antiviral effect (83)(84)(85)(86)(87).…”
Section: Discussionmentioning
confidence: 99%